Fundamentals of aerodynamics - Anderson, John David (McGraw-Hill series in aeronautical and aerospace engineering, 2011)
In keeping with its bestselling previous editions, Fundamentals of Aerodynamics, Fifth Edition by John Anderson, offers the most readable, interesting, and up-to-date overview of aerodynamics to be found in any text. The classic organization of the text has been preserved, as is its successful pedagogical features: chapter roadmaps, preview boxes, design boxes and summary section. Although fundamentals do not usually change over time, applications do and so various detailed content is modernized, and existing figures are replaced with modern data and illustrations. Historical topics, carefully developed examples, numerous illustrations, and a wide selection of chapter problems are found throughout the text to motivate and challenge students of aerodynamics.